Virtuale, Trascendenza E Immaginazione Teologica - S. I., Nicolas Steeves (Hermeneutica, 2020)
This article purports to show how the relation between the virtual, transcendence, and the imagination may receive new philosophical meaning through theological enquiry, made sharper by the global Coronavirus pandemic. Virtuality’s rich semantic history through Aristotelian metaphysics, physical optics, and digital technology casts a metaphysical doubt on its relation to reality. The imagination’s mediating function, seen in light of the theology of Christ’s mediation, can help peaceably overcome the false modern dichotomies that have arisen from a correct, but stymied understanding of reality’s complexities.